ANALISIS PENGARUH KUALITAS PRODUK, CITRA MEREK, VARIASI PRODUK DAN SUASANA TOKO TERHADAP KEPUTUSAN PEMBELIAN COFFEE SHOP DI KOTA BEKASI - Randy Reliantama Tanamas; Suwardi Suwardi (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the effect of product quality, brand image, product variety, and store atmosphere on purchasing decisions. The increasing number of people consuming coffee is clearly caused by the habits of modern society who enjoy gathering. Millennials and Gen Z now use coffee shops as places to drink coffee and interact with each other due to the shift in modern lifestyle. This study uses a sample of 100 respondents, namely customers or consumers of coffee shops in Bekasi City. The sampling method used is non-probability sampling with a purposive sampling technique. The testing stages conducted include validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, partial test (t-test), simultaneous test (f-test), and coefficient of determination test. The results of the study show that product quality, brand image, product variety, and store atmosphere simultaneously influence purchasing decisions. Product quality, brand image, product variety, and store atmosphere partially influence purchasing decisions.